CRITICAL REVIEW OF “INTERNATIONAL MONETARY RELATIONS: TAKING FINANCE SERIOUSLY” : by Maurice Obstfeld and Alan M. Taylor - Sandi, Gloria (SÉCULO XXI: Revista de Relações Internacionais - ESPM, 2022)
This is a Critical Review of the article "International Monetary Relations: Taking Finance Seriously", originally published by Maurice Obstfeld and Alan M. Taylor in the Journal of Economic Perspectives, in 2017. The autor Gloria Sandi reviews Obstfeld and Taylor’s explanation on the interactions between the international monetary and financial systems as an important determinant for the world to achieve its economic potential and to measure how grave are the prospects of crises and disruption, as well as their proposal of a financial policy trilemma.